DIFFUSION IN ZIRCON - Cherniak D.J.; Watson E.B. (My University, 2003)
Despite its low abundance in most rocks, zircon is extraordinarily useful in interpreting crustal histories. The importance of U-Th-Pb isotopic dating of zircon is well and long established (Davis et al., this volume; Parrish et al., this volume). Zircon also tends to incorporate trace elements useful as geochemical tracers, such as the REE, Y, and Hf. A number of characteristics of zircon encourage the preservation of internal isotopic and chemical variations, often on extremely fine scale, which provide valuable insight into thermal histories and past geochemical environments. The relative insolubility of zircon in crustal melts and fluids, as well as its general resistance to chemical and physical break-down, often result in the existence of several generations of geochemical information in a single zircon grain. The fact that this information is so frequently retained (as evidenced through back-scattered electron or cathodo-luminescence imaging that often reveal fine-scale zoning down to the sub-micron scale) has long suggested that diffusion of most elements is quite sluggish in zircon.